Impact of HY‐2B SMR radiance assimilation on CMA global medium‐range weather forecasts - Li, Zeting; Han, Wei (Quarterly journal of the Royal Meteorological Society, 2024)
The Chinese second ocean dynamic environment satellite Haiyang‐2B (HY‐2B) was successfully launched on October 25, 2018, carrying a scanning microwave radiometer (SMR) to provide information about the ocean and atmosphere. For the first time, this study investigated the impact of radiance data from the HY‐2B SMR in the four‐dimensional variational (4DVar) data assimilation system of the Global Forecast System developed by the China Meteorology Administration (CMA‐GFS). Prior to the radiance assimilation, we evaluated the data quality and developed suitable quality control (QC) procedures for the HY‐2B SMR observations. In addition, the cloud liquid water path (CLWP) and ocean wind speed (OWS) were introduced as new bias correction (BC) predictors to remove the systematic bias originating from the forward operator in the CMA‐GFS 4DVar system. The assimilation effects of SMR observations were evaluated through one‐month cycling experiments. Verification with independent observations and reanalysis data has demonstrated that assimilating SMR clear‐sky radiance can greatly reduce the analysis errors for temperature and humidity, while indirectly improving the quality of wind analysis. Furthermore, significant improvements in geopotential height forecasts were found for days 1–5 in the lower troposphere of the tropical region. The HY‐2B SMR is currently the only microwave imager operating in the early‐morning orbit for civil use, which could effectively fill the gap between the swaths of the microwave radiation imagers on board Fengyun‐3C and Fengyun‐3D. Various verifications demonstrate that the dynamic and thermodynamic fields are significantly improved in the analysis and forecasts after assimilating the SMR observations.